Education policy and governance in England under the Coalition Government (2010–15): Academies, the pupil premium, and free early education. (18th September 2015) - West, Anne
Abstract : This paper explores the governance of school-based and early education in England under the Conservative–Liberal Democrat Coalition Government (2010–15). It draws on three prominent Coalition policy areas – the academies programme, the pupil premium, and free part-time early education – and focuses on changes to the role played by central government in governance; in so doing, it also makes contrasts with Wales and Scotland. An analysis of the funding and regulatory framework reveals that the role of central government in England increased under the Coalition Government and that of local government declined. These changes to governance have served to centralize power on the one hand, and to facilitate and sustain markets in school-based and free early education on the other; the same cannot be said of governance in either Scotland or Wales, where democratically elected local government continues to play a highly significant role.